International and intercultural public relations: a campaign case approach / Baby Anusha Nur Mohamed Thaheer - Mohamed Thaheer, Baby Anusha nur (Faculty of Communication and Media Studies (FCMS), 2008)
Need to understand more about international public relations? Then this book International and Intercultural Public Relations: A Campaign Case Approach might interest you. It contains a complete guide on how to apply concepts to evaluate Public Relations activities and campaigns by providing examples of case studies and analyse of Public Relations cases.